MODULATION OF CARCINOGEN-METABOLIZING ENZYME BY MADINAH MINT (Mentha spp) IN RAT LIVER - Al-Malki, Abdulrahman L.; Barbour, Elie K.; A, Huwait E; Moselhy, Said S.; Choudhry, Hani (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The present study was undertaken to assess whether boiling water mint extract (BWME) modulates the cytochromeP450 mixed function oxidase system.Materials and methods: Male albino rats were randomly divided into two groups, comprising 12 animals each. The first groupserved as control, whereas the second was maintained on BWME (10 % w/v) as its sole drinking liquid for six weeks. Livermicrosomal were separated and subjected for phase I and II enzymes (cytochrome P450 mixed function oxidase) analysisResults The results obtained showed that, BWME caused a significant elevation in the activity of epoxide hydrolase (p<0.001) whencompared with the control. However, glutathione S-transferase and glucuronosyl transferase activities were significantly decreased(p<0.001 and p<0.01) respectively compared with control. The mutagenic activity of N-nitrosopiperidine was lower in the minttreatedhepatic microsomal compared with the controls.Conclusion: It can be concluded that BWME has the potential to suppress the activity of cytochrome enzymes involved in the bioactivationof chemical carcinogen; hence may display chemo preventive activity.